The PROMIS Physical Function Item Bank Was Calibrated to a Standardized Metric and Shown to Improve Measurement Efficiency - Rose, Matthias (J Clin Epidemiol, 2014)
OBJECTIVE: To document the development and psychometric evaluation of the Patient-Reported Outcomes Measurement Information System (PROMIS) Physical Function (PF) item bank and static instruments. STUDY DESIGN AND SETTING: Items were evaluated using qualitative and quantitative methods. 16,065 adults answered item subsets (n>2,200/item) on the Internet, with over-sampling of the chronically ill. Classical test and item response theory (IRT) methods were used to evaluate 149 PROMIS PF items plus 10 SF-36 and 20 HAQ-DI items. A graded response model was used to estimate item parameters, which were normed to a mean of 50 (SD=10) in a US general population sample. RESULTS: The final bank consists of 124 PROMIS items covering upper, central, and lower extremity functions and IADL. In simulations, a 10-item Computerized Adaptive Test (CAT) eliminated floor and decreased ceiling effects, achieving higher measurement precision than any comparable-length static tool across four standard deviations of the measurement range. Improved psychometric properties transferred to the CAT’s superior ability to identify differences between age and disease groups. CONCLUSION: The item bank provides a common metric and can improve the measurement of PF by facilitating the standardization of PRO measures and implementation of CATs for more efficient PF assessments over a larger range.